2013
DOI: 10.1016/j.jevs.2012.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Rider and Horse Salivary Cortisol Levels During Competition and Impact on Performance

Abstract: a b s t r a c tDuring competition, stress may affect riders and horses. This stress can affect health, welfare, and/or performance. Our aim was to quantify stress levels during competition in horses and riders. We also searched relationships between these stress levels and performance. Twenty riders and 23 horses were followed up during a show-jumping event (26 courses) held at a riding school. Regular saliva samples taken from horses and riders were assayed to evaluate cortisol levels. We studied salivary cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 26 publications
9
56
3
1
Order By: Relevance
“…The levels of salivary cortisol after feeding and after the novel object tests (range: 0.6-2.2 nmol/l) fell within the range of previously reported levels after mild stressors have been applied (reported ranges: 0.8-2.6 nmol/l; Pell and McGreevy, 1999;Shanahan, 2003;Harewood, 2005;Peeters et al, 2013;Becker-Birck et al, 2013). Becker-Birck et al (2013) highlighted that short term stress situations, such as show jumping do not show cortisol levels near the levels shown during one hour of travelling in a horse box (e.g.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The levels of salivary cortisol after feeding and after the novel object tests (range: 0.6-2.2 nmol/l) fell within the range of previously reported levels after mild stressors have been applied (reported ranges: 0.8-2.6 nmol/l; Pell and McGreevy, 1999;Shanahan, 2003;Harewood, 2005;Peeters et al, 2013;Becker-Birck et al, 2013). Becker-Birck et al (2013) highlighted that short term stress situations, such as show jumping do not show cortisol levels near the levels shown during one hour of travelling in a horse box (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…In future, measures such as spontaneous eye blink rate may be useful to establish dopaminergic function as a basic assessor of 'status' prior to selection of sample horses for behavioural studies (Colzato et al, 2009). Salivary cortisol was within the range of previously reported studies at base level (reported ranges of 0.8-1.18 nmol/l; Becker-Birck et al, 2013;Peeters et al, 2013;Young et al, 2012;Schmidt et al, 2010). Hart (2012) highlights the possible danger in over-interpreting the link between cortisol levels and perception of stress due to effects of animal age, individuality, experiences and daily environmental changes.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Peeters et al (2013) reported that cortisol value in saliva was between 1.18 and 1.92 nmol / l for horses during the rest and the competition. Figure 3 represents the comparison the content of cortisol in saliva on tested horses before and after the lunging.…”
Section: Horse Characteristicsmentioning
confidence: 99%